Application of Nimbadi Ointment after Chhedankarma in the Management of Gudavidradhi-A Case Study - R. Sharma, Varsha; Patel, Jigna; Padadhariya, Dhruval; Kazi, Wasim (Asian Journal of Pharmaceutical Research and Development, 2023)
Phenomena of vidradhi formation is due to vitiation of dosha resides in asthi and spreads and vitiates to the twacha, rakta, mamsa, meda and gradually reformed into excessively severe inflammatory swelling, which is maha-mulam (deep rooted), rujavantam (severe painful) vruttam (round) or aayatam (elongated in shape) that is calledvidhradhi1. In case of pei-anal abscess, originates from an infection arising in the crypto glandular epithelium lin-ing of the anal canal spreading into adjacent space and resulting in fistulas 40% of cases. Sheegravidahitvat definition of Vidradhi means virulence of disease. Acharya Sushruta mentions that if vidradhi attains pakvaavastha, the first line of treatment is to drain the pus through bhedana and later, it should be treated as Vrana. In the present context, a 52 years old male suffering from left sided gluteal abscess was admitted and treated with surgical incision and drainage This case ofanal abscess (gudavidradhi) so,application of nimbadi ointment after bhedankarma (incision and drainage) is the line of treatment.